2018
DOI: 10.1002/jso.24960
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of open and closed abdomen techniques for the delivery of intraperitoneal pemetrexed using a murine model

Abstract: Peritoneal absorption of pemetrexed is not modified by the use of either technique. However, systemic concentrations of pemetrexed increased using the open technique, suggesting it could increase systemic toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…While open vs. closed techniques have not been directly compared in humans, a murine model study in 2018 demonstrated some important potential differences. Eleven male rats received fixed-dose intraperitoneal pemetrexed at perfusion temperature of 40 ℃ for 25 minutes via open or closed techniques (39). Postoperative drug concentration in the portal blood, systemic blood and peritoneal tissue were measured.…”
Section: Surgical Approachesmentioning
confidence: 99%
“…While open vs. closed techniques have not been directly compared in humans, a murine model study in 2018 demonstrated some important potential differences. Eleven male rats received fixed-dose intraperitoneal pemetrexed at perfusion temperature of 40 ℃ for 25 minutes via open or closed techniques (39). Postoperative drug concentration in the portal blood, systemic blood and peritoneal tissue were measured.…”
Section: Surgical Approachesmentioning
confidence: 99%
“…Bowel anastomoses were performed after the HIPEC until 2008, when anastomoses were performed before the HIPEC. The open approach for HIPEC [14, 20] was performed until 2011, when all HIPECs were performed using the closed approach [21, 22]. Details of our HIPEC procedure has been previously described [14]; however, in brief, patients receive a systemic dose of fluorouracil (5-FU) (400 mg/m 2 ) and leucovorin (20 mg/m 2 ) 1 hour prior to HIPEC.…”
Section: Methodsmentioning
confidence: 99%
“…Depending on the origin of the used cancer cells, rat and mouse strains were chosen. The following rat types were used in the analyzed articles; Wistar (21%) [ 32 , 45 , 46 , 62 , 63 , 64 ], Sprague Dawley (32%) [ 40 , 43 , 51 , 52 , 57 , 65 , 66 , 67 , 68 ], WAG/Rij (32%) [ 47 , 54 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ] and athymic/nude (14%) [ 44 , 76 , 77 , 78 ] rats. For mouse experiments, the following strains were used: Swiss albino (20%) [ 36 , 38 , 79 ], athymic (33%) [ 37 , 48 , 50 , 55 , 80 ], C57BL/6 (20%) [ 33 , 39 , 81 ], BALB/c (20%) [ 49 , 56 , 82 ] and NOD-SCID (7%) [ 34 ].…”
Section: Preclinical Hipec Modelsmentioning
confidence: 99%
“…The effect of the delivery technique on the temperature or drug distribution was not assessed. Badrudin et al treated eleven rats with pemetrexed for 25 min at 40 °C using either the open or closed delivery techniques [ 57 ]. Peritoneal tissue concentration showed no difference, but higher systemic concentrations were observed using the open delivery technique, suggesting it could increase systemic toxicity.…”
Section: Physiological and Anticancer Aspects Of Preclinical Hipec Modelsmentioning
confidence: 99%